Inter-textual Analysis of Political Discourse in Party Manifestos - Malghanim, Mehwish; Khan, Faria Saeed; Yousaf, Saima; Akarm, Zainab (Al-Burz, 2017)
Political discourse is inarguably deemed an essential tool, influencing people’s perception within a socio-political zone in an imperceptible manner. The present research titled “Inter-textual Analysis of Political Discourse in Party Manifestos” revolved around a critical discourse analysis of manifestos, as presented by five most popular Pakistani political parties, pertaining to the general election, held during the year 2013. With regard to the present context, the mentioned pursuit primarily aimed at linguistically analyzing the political discourse of the aforementioned manifestos at inter-textual level. The theoretical framework used to substantiate the overall analysis centered on Fairclough’s theory of intertextuality (1995) and van Dijk Ideological Square(2004). The findings of the research revealed that all the political parties under study, brought into use the discursive strategy of intertextuality in their party manifestos in order to enhance the positive self image of party to in-group people, by hunting the negative aspects of the out-group, thereby (re)constructing people’s political identities and ideologies and achieving the desired hegemony in a way peculiar to itself. Research of the kind can be conducted further by analyzing the other dimensions of political discourse and the resultant ideologies, influencing the current state of affairs as prevalent around the globe with special focus on the linguistic aspects of the political discourse.